Prevalence of and Factors Related to Prescription Opioids, Benzodiazepines, and Hypnotics among Medicare Home Health Recipients - Cotton, Brandi Parker (Home Healthc Now, 2017)
High rates of controlled prescription drugs are associated with cognitive impairment, falls, and misuse and dependence. Little is known about the prevalence of these medications among older adults receiving home healthcare. The purpose of this study was to determine the frequency of, and the factors related to, opioid analgesics, benzodiazepines (BNZ), and non-benzodiazepine (NBNZH) hypnotics among a large sample of older adults entering home health services. The data came from administrative records of 133 Certified Home health Agencies located across 32 states. Patients (age ≥ 65) receiving Medicare home health services and who received a start-of-care Medicare OASIS assessment between Jan. 1, 2013 and Dec. 31, 2014 were included in the study (n= 87,780). Rates of controlled medication use were compared across patient-level sociodemographic, clinical, functional, and environmental variables. The prevalence of controlled medication was high, with 58% prescribed at least one class of controlled drug, 44% were prescribed an opioid, 19% were prescribed a BNZ, and almost 7% were prescribed a NBZDH. Factors independently associated with higher levels of controlled medication usage include younger-old age, white race, post-surgical status, injuries, referral from inpatient settings and rural location. Home health clinicians are well-positioned to review and reconcile medication, oversee referrals and follow-up care, and provide ongoing assessment of risk regarding the use of opioids, BNZ, and hypnotics among home health patients.